Investigation of tensile twinning on texture and microstructure evolution of Mg-3Al-1Zn-1Ca alloy under in-plane shear deformation - Saurav Kumar; Mahesh Panchal; Appala N. Gandi; Lalit Kaushik; Shi-Hoon Choi; Jaiveer Singh (Journal of Magnesium and Alloys)
The evolution of microstructure and texture in Mg-3Al-1Zn-1Ca alloy sheets subjected to in-plane shear (IPS) loading was investigated using experimental techniques and viscoplastic self-consistent (VPSC) modeling. The specimens were deformed under varying degrees of IPS strain (γ₁₂ = 0.05, 0.10, and 0.15) using a customized jig. Electron backscatter diffraction (EBSD) observations revealed profuse tensile twinning (TTW) even at an IPS strain of 0.05, with its intensity continuously increased as the IPS strain increased. The TTWs progressively engulfed parent grains with increasing shear strain, evolving into an unusual deformation twin morphology. Furthermore, VPSC model predictions confirmed basal slip as the dominant deformation mode at low IPS strains, transitioning to prismatic slip dominance at higher IPS strains. The activity of the TTW mode was significantly higher during the initial stages of IPS strain and saturated to lower values at higher strains. VPSC simulation results also indicated preferential shear accumulation on a single twin system, explaining the phenomenon of a single twin variant engulfing a parent grain. Additionally, the influence of individual slip and twin modes on texture evolution was evaluated through orientation tracking of representative grains at various shear strain increments using VPSC simulation. The simulation results quantitatively highlighted the activities of basal slip, prismatic slip, and tensile twinning, establishing a correlation between texture evolution and the underlying deformation mechanisms.